2007
DOI: 10.1038/modpathol.3800753
|View full text |Cite
|
Sign up to set email alerts
|

Ossifying fibroma vs fibrous dysplasia of the jaw: molecular and immunological characterization

Abstract: Ossifying fibroma and fibrous dysplasia of the jaw are maxillofacial fibro-osseous lesions that should be distinguished each other by a pathologist because they show distinct patterns of disease progression. However, both lesions often show similar histological and radiological features, making distinction between the two a diagnostic dilemma. In this study, we performed immunological and molecular analyses of five ossifying fibromas, four cases of extragnathic fibrous dysplasia, and five cases of gnathic fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
126
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(143 citation statements)
references
References 25 publications
5
126
0
8
Order By: Relevance
“…18,[35][36][37][38][39][40] Okada et al 41 studied eight cases of low-grade central osteosarcomas retrospectively and showed that proliferative cell activity evaluated by AgNOR and MIB-1 immunohistochemical staining was significantly higher in cases of low-grade central osteosarcoma than in fibrous dysplasia and might be helpful in differentiating low-grade central osteosarcoma from fibrous dysplasia. Pollandt et al 42 showed that Gsalpha gene mutations were a constant finding in cases of monostotic fibrous dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…18,[35][36][37][38][39][40] Okada et al 41 studied eight cases of low-grade central osteosarcomas retrospectively and showed that proliferative cell activity evaluated by AgNOR and MIB-1 immunohistochemical staining was significantly higher in cases of low-grade central osteosarcoma than in fibrous dysplasia and might be helpful in differentiating low-grade central osteosarcoma from fibrous dysplasia. Pollandt et al 42 showed that Gsalpha gene mutations were a constant finding in cases of monostotic fibrous dysplasia.…”
Section: Discussionmentioning
confidence: 99%
“…The details of the 24 studies are summarized in Table 3. 1, Among the 24 studies, the numbers of cases ranged from 1 to 64, various techniques have been used for the detection of GNAS mutations, such as reverse transcription PCR and clone sequencing, conventional PCR and direct sequencing, PCRrestriction fragment length polymorphism, pyrosequencing, PCR with mutation-specific restriction enzyme digestion and so on. A variety of materials were used for the extraction of genomic DNA, including fresh bone biopsy, fresh bone tissue, lesional stromal cell cultures, formalin-fixed, paraffin-embedded tissues and so on.…”
Section: Gnas Mutationsmentioning
confidence: 99%
“…In the 13 studies that mentioned the types of the bone involved, 1,13,16,17,19,21,23,27,28,30,31,33,34 the positive rate of GNAS mutation was 84% in the extragnathic bones and 78% in the craniofacial bones.…”
Section: Gnas Mutationsmentioning
confidence: 99%
See 2 more Smart Citations